Evolution of Edge-On Oriented Polymer Films Self-Assembled at the Air-Liquid Interface for High-Performance Electronic Device Applications - Jana S.; Pandey R.K.; Prakash R. (My University, 2025)
In the context of semicrystal growth in thin films of organic semiconducting polymers (OSPs) at the air-liquid interface, polymer self-assembly is mainly governed by convective Marangoni flow, compressive viscous force, divergent evaporation flux, and high conformational degrees of freedom of OSPs, which lead to a very complex microstructure having many cumulative and noncumulative disorders. In this regard, first time, major polythiophene derivatives such as poly(3-hexylthiophene-2,5-diyl) (P3HT), poly(3,3‴-didodecyl[2,2′:5′,2″:5′′,2′′′-quaterthiophene]-5,5′′′-diyl) (PQT), and poly[2,5-bis (3- tetradecylthiophen-2-yl) thieno[3,2-b]thiophene] (PBTTT) are collectively employed as model OSPs to explain film growth on aqueous substrates and examined using multiple characterization techniques. At first, we have investigated the degree of paracrystalline disorder along (h00) direction in three different polymer backbone structures. Then, the local in-plane orientation of the polymer chains in crystalline domains along the π-πstacking direction has been studied using the bright field HR-TEM images. Moreover, quantum mechanical penetration of localized trap states into the bandgap induced by those structural imperfections has also been quantified from optical property measurements. Finally, we have studied the charge transport properties in all three directions (out-of-plane and in-plane viz. along and across the polymer chains) of the thin solid polymeric films using vertical and planar device architectures. We have observed maximum out-of-plane mobility (μh) 3.7 × 10-5cm2/V·s for P3HT, and in-plane mobility, μh(along the polymer chains) 0.234 cm2/V·s for PBTTT. By considering the obtained results from different characterizations and all possible flow processes, we have tried to propose the exact growth mechanism of these thin films. Thus, our findings give an insight into the fundamentals of polymer self-assembly to a structure-property correlation, which is extremely important for material processing and device engineering to meet the growing technological appeal. © 2022 American Chemical Society.